Expressão psicossomática da infertilidade conjugal: investigação dos processos de enfrentamento durante diagnóstico - Souza, Solange Lopes de (2005)
This study examined the process of coping with conjugal infertility during diagnostic investigation offered to 30 couples. Instruments addressed to investigation of life events, such as SF-36 General Life Quality Instrument, instrument about coping strategies, questionnaire about the couples clinical history, questionnaire about diagnostic medical evaluation and a rule for semi structured interview concerning the process of coping with infertility, have been used. The interviews have been recorded, transcribed, and analyzed by using SPAD T program. Afterwards, the meanings attached by the couples to the experience they were living in the search for having a biological child, so as personal meanings and senses of motherhood, fatherhood and the importance of a child in their lives, have been verified. As showed by the analyses of the instrument about coping strategies, there was low use of the eight factors under investigation; the more frequently used among them were: the ones which require self control, search for social support, problem solving, and positive revaluation. No differences have been verified between men and women. Analyses of SF-36 General Life Quality Instrument showed that couples life quality lay between good and excellent conditions. Significance level of functional aptitude, vital force, social issues, mental health, and pain has been observed in the female group; the male group showed significance levels of general health state, physical limitation, functional aptitude, pain, vital force, and mental health. Analyses about occurrence of life events showed low reports or absence of significant changes in the couples life, such absence being an indicator to risk factor and a sign of alert to possibilities of distress development. An important factor has been identified at the moment of the semi structured interview concerning identification of available forms and resources of coping. Analyze of the speech produced by the couples showed that they presented a lack of syntony in the quality of their relationship, what produced interferences on mutual support during the search for a solution to problems to be faced, specifically when it concerned infertility. Suggestions of programmed sexual intercourse showed themselves as a factor that interferes on stability of personal relationship. It brings difficulties to the couple. To think about the meanings of a child has become a shocking exercise. This fact is probably associated to the function that is still attributed to a biological child as someone who would legitimate affective relationships, the possibility of which being questioned when a child is adopted. Semi structured interview has showed itself as an essential instrument to investigate and fathom coping factors. This resource promoted a different hearing of anxiety, making possible a better reflection to the couples about coping with their difficulties when facing investigation and treatment of infertility